Aflatoxin B1 Occurrence, Detection and Toxicological Effects 2020
DOI: 10.5772/intechopen.88582
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin Occurrence in Dairy Feeds: A Case of Bulawayo, Zimbabwe

Abstract: Aflatoxin contamination in feeds used by Bulawayo peri-urban farmers for dairy cows was assessed. Semi-intensive farming was the most common farming type practised by the farmers where the animal feeds were supplemented with mixed rations, concentrated feed, grass and brewers' spent grains. Mixed ration was the most commonly used feed supplement. Feed analysis by highperformance liquid chromatography (HPLC) showed the presence of all four naturally occurring aflatoxins: aflatoxins B 1 , B 2 , G 1 and G 2 . Tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…Authors have reported with certainty that climate change is the main agro-ecological driving force of fungal colonisation and mycotoxin production [ 14 , 15 ]. Fungi colonise many crops and are adapted to a wide range of environmental conditions, with specific as well as overlapping ecological niches [ 16 ].…”
Section: Factors Responsible For High Levels Of Mycotoxin Contaminati...mentioning
confidence: 99%
“…Authors have reported with certainty that climate change is the main agro-ecological driving force of fungal colonisation and mycotoxin production [ 14 , 15 ]. Fungi colonise many crops and are adapted to a wide range of environmental conditions, with specific as well as overlapping ecological niches [ 16 ].…”
Section: Factors Responsible For High Levels Of Mycotoxin Contaminati...mentioning
confidence: 99%
“…As climatic conditions undergo significant shifts, ecosystems experience alterations in temperature, precipitation, and humidity, all of which create conducive environments for fungal proliferation and subsequent mycotoxin synthesis (Achaglinkame et al, 2017;Nleya et al, 2020). Fungi inhabit numerous crops and exhibit adaptability to diverse environmental conditions, occupying distinct ecological niches that may overlap (Perrone et al, 2020).…”
Section: G Environmental Factorsmentioning
confidence: 99%
“…Global warming is significantly driving altered temperature distributions and extreme precipitation patterns. Agreement exists on the important role of drought, high temperatures, and extreme precipitation patterns on increased AF production in maize [10][11][12][13]. Other studies have found significant correlation between increased AF levels and insect-damaged crops [14,15].…”
Section: Introductionmentioning
confidence: 99%